GAMBARAN PERILAKU PETUGAS RAWAT INAP DALAM PELAKSANAAN PROMOSI KESEHATAN RUMAH SAKIT (PKRS) DI RUMAH SAKIT UMUM DAERAH TANJUNG PURA KABUPATEN LANGKAT TAHUN 2012 - yusrida fadma lubis; Syarifah .; R.Kintoko Rochadi (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
Abstract The effectiveness of  a treatment is not only influenced by the existing pattern of health service but also by the attitude and skills in its implementation. Hospital Health Promotion is an attempt taken by a hospital to improve the ability  of patients, clients, and community group that the patients can be independent in improving their health and preventing health problems through learning from, by, for and together in accordance wih their social culture supported by health-oriented public policy. The purpose of this descriptive quantitative study was to find out the description of how thw health workers working in the in-patient wards behave in the implementation of Hospital Health Promotion at Tanjung Pura General Hospital, Langkat District. The population of this study was all of the 71 health workers who implemented the Community Health Promotion program at Tanjung Pura General Hospital and 71 of them working in the in-patient wards were selected to be the samples/respondents for this study. The data for this study were obtained through questionnaire-based interviews. The result of thus study showed that 27 respondent (38%) had inadequate knowledge about the Hospital Health Promotion, (42,3%) had good attitude, and 53 respondents, 30 respondents (74,6%) had taken less action. Therefore, the behavior and knowledge of the health workers needs to be improved through upgrading and training or providing the health workers with literatures related to Hospital Health Promotion. Keywords: Healths Workers Behavior, Health Promotion, Hospital